(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: In 2020 there were estimated to be 25 million deaths each year from cardiovascular disease; most of them being coronary heart disease. Traditional risk factors such as smoking, hypertension, diabetes, dyslipidemia reported to affect only 50% of the prevalence and degree of coronary heart disease. It pushes a lot of research on non-traditional risk factors one of which is lipoprotein (a). Levels of Lp (a) also reflects the degree of severity and is associated with the number of coronary arteries involved. The purpose of this study was to determine the relationship of Lp (a) level with the complexity of coronary artery lesion. Methods: This was a cross-sectional study. Subjects were male and women patients aged between 20 to 60 years who underwent coronary angiography for theirs STEMI, NSTEMI, unstable angina pectoris, and stable angina pectoris. Correlation between elevated Lp (a) with the complexity of coronary artery lesion was performed by Pearson test. If the distribution was abnormal we used Spearman test. Result: Number of samples was 64 subjects (49 men and 15 women). The result showed a significant positive correlation between Lp (a) level and complexity of coronary vessel lesion that counted by SYNTAX score (p 0,004) even though the coefficient correlation is weak (r 0, 33). Conclusion: The higher Lp (a) level shows bigger SYNTAX score which means the coronary vessel lesion more complex. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.362-367